2012
DOI: 10.1016/j.cellsig.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

TNFα and SOCS3 regulate IRS-1 to increase retinal endothelial cell apoptosis

Abstract: Rates of diabetes are reaching epidemic levels. The key problem in both type 1 and type 2 diabetes is dysfunctional insulin signaling, either due to lack of production or due to impaired insulin sensitivity. A key feature of diabetic retinopathy in animal models is degenerate capillary formation. The goal of this present study was to investigate a potential mechanism for retinal endothelial cell apoptosis in response to hyperglycemia. The hypothesis was that hyperglycemia-induced TNFα leads to retinal endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 46 publications
1
73
0
Order By: Relevance
“…1,5 It also regulates endothelial cell (EC) apoptosis. 4 However, the role of SOCS3 in regulating angiogenesis in vivo is unknown. If SOCS3 were angiostatic, as has been hypothesized, then its suppression would increase neovascularization in pathologic conditions (see Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 It also regulates endothelial cell (EC) apoptosis. 4 However, the role of SOCS3 in regulating angiogenesis in vivo is unknown. If SOCS3 were angiostatic, as has been hypothesized, then its suppression would increase neovascularization in pathologic conditions (see Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 SOCS3 is transiently induced by inflammatory mediators such as lipopolysaccharide, 3 IL-6, 3 and TNF␣. 4 SOCS3 inhibits cytoplasmic effectors such as the JAK/STAT kinases and deactivates tyrosine kinase receptor signaling, including the IGF-1 receptor. 1,5 It also regulates endothelial cell (EC) apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…miR15a decreased tumor necrosis factor alpha (TNFα) levels, which can help to restore normal insulin signaling (Jiang et al, 2012, 2018). In addition to TNFα, other inflammatory cytokines, such as IL-1β, are also upregulated in diabetic retinopathy and indicated in diabetic complications (Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that β-adrenergic receptors can regulate TLR4 in the diabetic retina, as well as retinal endothelial cells (REC) an Müller cells [7]. Additionally, we have reported that a β-adrenergic receptor agonist can reduce functional, neuronal, and vascular phenotypes associated with retinopathy with rodents [8], as well as restore normal insulin signal transduction in cells grown in high glucose [9, 10]. …”
Section: 0 Introductionmentioning
confidence: 99%